1996
DOI: 10.1097/00006123-199607000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Details of Intradural Channels in the Parasagittal Dura: A Possible Pathway for Flow of Cerebrospinal Fluid

Abstract: These channels may represent a pathway for the flow of cerebrospinal fluid from AG to the SSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 19 publications
2
51
0
Order By: Relevance
“…Homogeneously hyperdense SDH was present in fewer than one-third of our cases; mixed-density SDH, containing both hyperdense and hypodense components, was present in over half of the infants in the present study, in onethird of children in our prior study, 9 and in 91% of infants with AHT in a third study by Vinchon et al 31 Mixeddensity SDH in AHT has been interpreted as prima facie evidence of serial injuries, 6,25 but this concept has recently been challenged. 9,11,32,33,39 One child in our previous study developed a hypodense subdural collection de novo on a second CT scan performed 19 hours after an initial scan showed no SDH in that region. 9 In another study of 18 infant victims of motor vehicle crashes with SDH, 3 infants had mixed-density SDH on the initial CT scan.…”
Section: Serial Changes On Ctmentioning
confidence: 85%
See 1 more Smart Citation
“…Homogeneously hyperdense SDH was present in fewer than one-third of our cases; mixed-density SDH, containing both hyperdense and hypodense components, was present in over half of the infants in the present study, in onethird of children in our prior study, 9 and in 91% of infants with AHT in a third study by Vinchon et al 31 Mixeddensity SDH in AHT has been interpreted as prima facie evidence of serial injuries, 6,25 but this concept has recently been challenged. 9,11,32,33,39 One child in our previous study developed a hypodense subdural collection de novo on a second CT scan performed 19 hours after an initial scan showed no SDH in that region. 9 In another study of 18 infant victims of motor vehicle crashes with SDH, 3 infants had mixed-density SDH on the initial CT scan.…”
Section: Serial Changes On Ctmentioning
confidence: 85%
“…31 Several authors have hypothesized that mixed-density SDH may reflect an admixture of fresh clotted blood, unclotted blood or serum, and/or CSF from the subarachnoid space that has migrated into the subdural space through a tear in the arachnoid membrane. 9,11,33,39 A communication between the subarachnoid and subdural spaces in infants with SDH was confirmed in one study by injecting a radioisotope into the CSF via lumbar puncture at the time of subdural drain placement and identifying the radioisotope within the subdural fluid within 3-24 hours. 39 It is apparent that although mixed-density SDHs are more common after AHT, and some of these likely represent acute and prior injuries, the fact that they are also present early after presumably single accidental injuries makes their interpretation more difficult.…”
Section: Serial Changes On Ctmentioning
confidence: 94%
“…All had characteristic pattern of biochemical abnormality including low plasma urate and high urinary sulphite, xanthines/ sulphocysteine. Burst suppression was seen in the neonatal period in all those who had EEG during this time (3).…”
mentioning
confidence: 72%
“…Recent resin injection studies have demonstrated a network of channels draining into the venous sinuses in close proximity to arachnoid granulations which are generally assumed to resorb CSF 2,3 . CSF resorption routes are poorly understood and a route via the dura has been suggested 4 .…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation